Molecular Phylogenetics and Micromorphology of Australasian Stipeae (Poaceae, Subfamily Pooideae), and the Interrelation of Whole-Genome Duplication and Evolutionary Radiations in This Grass Tribe - Tkach, Natalia; Nobis, Marcin; Schneider, Julia; Becher, Hannes; Winterfeld, Grit; Jacobs, Surrey W. L.; Röser, Martin (Frontiers in Plant Science, 2021)
The mainly Australian grass genus Austrostipa (tribe Stipeae) comprising approximately 64 species represents a remarkable example of an evolutionary radiation. To investigate aspects of diversification, macro- and micromorphological variation in this genus, we conducted molecular phylogenetic and scanning electron microscopy (SEM) analyses including representatives from most of Austrostipa’s currently accepted subgenera. Because of its taxonomic significance in Stipeae, we studied the lemma epidermal pattern (LEP) in 34 representatives of Austrostipa. Plastid DNA variation within Austrostipa was low and only few lineages were resolved. Nuclear ITS and Acc1 yielded comparable groupings of taxa and resolved subgenera Arbuscula, Petaurista, Bambusina in a common clade and as monophyletic. In most of the Austrostipa species studied, the LEP was relatively uniform (typical maize-like), but six species had a modified cellular structure. The species representing subgenera Lobatae, Petaurista, Bambusina as well as A. muelleri from subg. Tuberculatae were well-separated from all the other species included in the analysis. We suggest recognizing nine subgenera in Austrostipa (with number of species): Arbuscula (4), Aulax (2), Austrostipa (36), Bambusina (2), Falcatae (10), Lobatae (5), Longiaristatae (2), Petaurista (2) and the new subgenus Paucispiculatae (1) encompassing A. muelleri. Two paralogous sequence copies of Acc1, forming two distinct clades, were found in polyploid Austrostipa and Anemanthele. We found analogous patterns for our samples of Stipa s.str. with their Acc1 clades strongly separated from those of Austrostipa and Anemanthele. This underlines a previous hypothesis of Tzvelev (1977) that most extant Stipeae are of hybrid origin. We also prepared an up-to-date survey and reviewed the chromosome number variation for our molecularly studied taxa and the whole tribe Stipeae. The chromosome base number patterns as well as dysploidy and whole-genome duplication events were interpreted in a phylogenetic framework. The rather coherent picture of chromosome number variation underlines the enormous phylogenetic and evolutionary significance of this frequently ignored character.